Analisis Kemampuan Guru dalam Menangani Masalah dalam Belajar Mengajar di SMK Swasta Bandung Percut Sei Tuan - Sani Susanti; Hizkia Hosiana Simatupang; Jonatan Arvonsius Gultom; Parazt Hasibuan; Rifdah Syahbani Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Although it is hoped that school children are able to deal with learning situations well, in reality students often experience obstacles in the teaching and learning process, which shows a gap between expectations and educational reality. This research focuses on a teacher from the Bandung Percut Sei Tuan Private Vocational High School (SMK). The aim of this research is to identify and understand the problems faced by teachers in teaching and the approaches used to overcome these obstacles through in-depth and open interviews. Interviews were conducted in the teacher's work space, with the aim of creating an environment that supports and encourages teachers to share experiences and their thoughts openly. The interview guide consisted of five questions designed to explore the main challenges in teaching, conflict resolution strategies, and the teacher's ways of dealing with students' low interest or difficulty in following lessons. The teacher identified major challenges such as lazy attitude towards studying, tendency to sleep, and high interest in playing among students. In facing this challenge, teachers adopt a flexible approach by providing short breaks between intensive learning sessions to maintain students' energy and focus. In terms of conflict resolution, teachers emphasize the importance of patience and self-control, as well as providing positive reinforcement for desired behavior. Teachers also emphasize the need to treat students with compassion and emotional attention, seeing them as biological children who must be cared for and guided with care. In addition, teachers realize the importance of collaborating with parents to support students' holistic development. The research results show that the main challenges faced by teachers in teaching at the Bandung Percut Sei Tuan Private Vocational School can be overcome through a flexible approach, positive reinforcement, and deep emotional attention. This approach is believed to create an inclusive and supportive learning environment, which in turn can improve students' emotional well-being and academic achievement. This research provides important insights for educators in developing effective strategies to overcome obstacles in the teaching and learning process